(untitled) (Research, Society and Development, 2023)
After the beginning of the COVID-19 Pandemic, when analyzing the symptoms of the first cases of COVID-19, it was noted that the signs and symptoms most commonly presented by these patients were Gripal Syndromes. In addition, the presence of other clinical symptoms that were being presented by patients diagnosed with COVID-19 was also noticed, such as anosmia, hyposmia and dysgeusia, starting to be considered as relevant manifestations to be considered in the initial clinical diagnosis or the permanence after active infection of the disease. Based on this, the objective of this study was to elucidate changes in the sensory functions of smell and taste in patients diagnosed with COVID-19. In which, this research took place through an approach to the patients of a Pulmonology office in a teaching clinic of a private university in Teresina-PI. After the 133 interviewees, the results indicated that there was no persistence of smell and taste alterations, in most cases, being limited only to the acute phase of the infection. For this, the collected clinical data will contribute to the social context, in a way that will serve to update epidemiological data and knowledge for health professionals, with the purpose of guaranteeing better clinical assistance in evidence-based practice.